Socioeconomic and socioecological issues of the pandemic crisis in the Amazon - Lise Tupiassu; Ana Elizabeth Neirão Reymão; Jean-Raphaël Gros-Désormeaux (Revue de la Régulation, 2021)
The spread of covid-19 in the Amazon region urges us to reflect on how this can be related to forms of appropriation of the Amazon’s natural resources by global value chains. This article aims at discussing how the coronavirus pandemic has laid bare the vulnerabilities resulting from the Amazon’s insertion to global capitalism. Whether dependent on domestic or extraterritorial economic dynamics, no sector of activity and no community appears to be untouched by covid-19. The pandemic shows that revenues generated by economic activities such as mining and cattle breeding in the Amazon deeply depend on the international reach of their economic circuits, at the same time as on the non-observance of a number of fundamental rights of indigenous people. This clearly implies looking for alternatives to the unsustainable exploitation of nature and reconsidering the development model of the Amazon.